HUBUNGAN ANTARA SCHOOL WELL-BEING DAN KETERLIBATAN DALAM KEGIATAN BELAJAR PADA SISWA SMA KELAS 11 - Annisa Muliani; Lucia R. M. Royanto; Widayatri S. Udaranti (MANASA, 2012)
This research investigates the relationship between school well-being and the high school students’ involvement in learning. The participants are 579 year 11 students from 5 areas of Jakarta. The school well-being is assessed by an instrument developed by Konu (2002), which learning is assessed by a modified instrument of RAPS-S (Research Assessment Package for Schools-Student Report) which was developed by Institute for Research and Reform in Education. This instrument was also modified by Udaranti (2005), so it can be used for Indonesian situation. The result of this research shows that there is a positive and significant correlation between school well-being and student involvement. The aspects of school well-being which comprise of having, loving, and wellbeing are also related to students’ involvement in learning.